Les implications de la stabilisation de la construction résidentielle - Chung, Joseph; Chabot-Plante, Francine (L'Actualité économique)

(untitled) (HEC Montréal, 1975)
AbstractMonetary policy has been recognized as one of the principal reasons for cyclical instability in residential construction. It has been therefore suggested that residential construction should be isolated from monetary policy. This paper is designed to measure the impact of such suggestion.We have used the CANDIDE model for our experimentation. Residential construction is isolated through appropriate adjustments of the intercepts of the equations for residential construction. This led of cause of disturbances in various aggregates of the economy. Hence, a series of simulations was run in such a way that the disturbed aggregates would come close to the corresponding aggregates obtained by the control-solution. This meant additional adjustment in money supply and Treasury Bond yield, which are regarded as proper indicators of monetary policy.It was found that the additional adjustment varied between 9 to 16% in case of money supply and 38 to 45% in case of Treasury Bond yield. In addition, variation in non-residential construction and investment in machinery and equipment was found to be significant. In short, though efficient in stabilizing residential construction, the isolation of residential construction from monetary policy appears to be costly in terms of its impact on monetary policy and capital investment.